Sentencing Mentally Disordered Offenders: Lessons from the US and Singapore - CHUA, Eunice (Institutional Knowledge at Singapore Management University, 2011)
Mentally disordered offenders pose a unique challenge to criminal justice systems. Worldwide there is an observable trend of having a significant and rising number of mentally disordered offenders in prisons and other detention facilities. This article seeks to address how mentally disordered offenders are sentenced in the US and in Singapore, and discusses whether the present approach to sentencing suitably addresses the broad goals of the criminal justice system while taking into account the situation of mentally disordered offenders.